Benchmark experiments at YALINA-Thermal subcritical assembly - Kiyavitskaya, Hanna I. (Journal of the Belarusian State University. Ecology, 2020)
Description of the benchmark at the subcritical assembly YALINA-Thermal in the JIPNR-Sosny NAS of Belarus is presented at this paper. The results of the international benchmark in the frame of the IAEA* Research Contract and the International Science&Technology Center B-070 “Experimental and theoretical investigations of the peculiarities of transmutation of long-lived fission products and minor actinides in a subcritical uranium-polyethylene assembly driven by a neutron generator” are described in this work.
Keywords: subcritical systens; benchmark; uranium-polyethylene assembly YALINA-Thermal; kinetic characteristics; neutron spectrum; nuclear fuel cycle; transmutation